Communicative Applications in the Websites of the Iraqi Political Parties and their Role in Providing Opportunities for Political Participation - حداد, حسين اسماعيل (ALBAHITH ALALAMI, 2015)
The present study deals with the websites of Iraqi political parties on the internet to identify the effectiveness in providing communicative applications that help audience to participate, express their opinions, their positions, and other aspects reflecting the extent of employing modern technological tools to allow opportunities for political, and democratic participation since the internet has become an effective tool for political communications of political parties. The research sample includes eight political parties. The research concludes that the Iraqi political parties do not employ interactive communication patterns to reflect their interests in communicating with the public, providing opportunities for their participation and recognizing their attitudes through their websites. These websites serve as media function of one way rather than as an interactive communicative function with the users.